Cross-cultural adaptation and validation of the RhinAsthma Patient Perspective (RAPP) in Spanish - Ansotegui, I J; Braido, F; Molinengo, G; Loera, B; Gonzalez-Diaz, S; Sanchez-Borges, M; Canonica, G W; Baiardini, I (Allergologia et immunopathologia, 2020)
the RhinAsthma Patient Perspective (RAPP) is the only available tool to assess HRQoL in daily practice. The aim of this study is to cross-culturally validate the RAPP in Spanish. The RAPP was translated into Spanish. Adult patients receiving usual care for asthma and allergic rhinitis (AR) were recruited consecutively and assessed twice with a four-week interval between visits to test the psychometric properties of the questionnaire. 149 patients (62.8% female) with a mean age of 37.7 years completed the study. Exploratory and confirmatory factor analysis confirmed the uni-dimensional structure of the questionnaire. Internal consistency (0.73 at visit 1; 0.87 at visit 2), convergent and discriminant validity (p<.05 at both visits) were satisfactory. Reliability was confirmed by an ICC of 0.69 and a CCC of 0.74. Responsiveness was supported by a significant association with VAS (r=0.28, p<0.003) and ACT (r=-0.35, p<0.01). The minimal clinical difference (MID) value in the analyzed population was 2. The Spanish version of RAPP was demonstrated to have satisfactory psychometric properties and is a valid, reliable and responsive tool for the assessment of asthma and AR HRQoL in clinical practice.